All-solid-state lithium ion battery positive electrode material as well as preparation method and application thereof

The Li2S+FeCl3 composite material was synthesized by high-energy ball milling method and in-situ sulfur was introduced, which solved the interface problems and low energy density of the positive electrode materials of all-solid lithium-ion batteries, achieved high energy density and good cycle stability, and had good industrialization Application prospects.

CN119315016AActive Publication Date: 2025-01-14DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411834700.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-01-14
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

The positive electrode materials of all-solid-state lithium-ion batteries have interface problems and low energy density, resulting in insufficient cycle stability and energy density, limiting the room for improvement of the battery system.

Method used

The Li2S+FeCl3 composite material was synthesized by high-energy ball milling method, and the in-situ introduction of sulfur to form a stable interface, which increased the voltage platform and energy density, and reduced the use of conductive agents and supporting electrolytes through optimized composition and process.

Benefits of technology

It significantly improves the energy density and cycle stability of the battery, reduces the voltage difference of the voltage platform, simplifies the process, and has good industrial application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119315016A_ABST
    Figure CN119315016A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of all-solid-state lithium ion batteries, and particularly relates to an all-solid-state lithium ion battery positive electrode material as well as a preparation method and application thereof. Li2S and FeCl3 raw materials are taken and uniformly mixed; and under the protection of inert atmosphere, carrying out high-energy ball milling reaction on the obtained raw materials to obtain the positive electrode material. The high-energy-density multi-electron transfer positive electrode material can be applied to all-solid-state lithium ion batteries only by compounding 5% of conductive carbon and 25% of supporting electrolyte, and compared with a sulfur-based positive electrode material, the high-energy-density multi-electron transfer positive electrode material has obvious advantages in active substance proportion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of all-solid-state lithium-ion batteries, and in particular relates to all-solid-state lithium-ion battery positive electrode materials, preparation methods and applications. Background Art

[0002] Based on the dual carbon goals, vigorously developing new energy vehicles is conducive to reducing carbon emissions and thus achieving the dual carbon goals. As a key factor in the promotion of new energy vehicles, the performance of its power battery has attracted much attention. Its power battery energy density and safety are currently lacking in competitiveness compared with traditional vehicles. In order to improve the safety and energy density of lithium-ion batteries, it is necessary to explore new battery systems. All-solid-state lithium batteries can directly match lithium metal negative electrodes to have high energy density, and replace traditional flammable organic electrolytes with non-flammable solid electrolytes, which greatly improves the safety of power batteries and is a key technology for realizing new energy vehicles in the future. In addition, all-solid-state lithium batteries have other advantages, including high lithium ion mobility, regular geometric shapes, simple battery design, and a wide operating temperature range.

[0003] However, the large weight of the positive electrode material and the low theoretical capacity are the key factors limiting the battery system from further improving its energy density. Based on this, this paper summarizes the two key problems existing on the positive electrode side of current solid-state lithium batteries, namely, interface problems and low energy density.

[0004] Interface problems are divided into interface contact problems and interface side reaction problems. The former is based on the high interface impedance caused by the solid-solid contact pores and grain boundaries in the positive electrode material itself, while the latter is due to additional side reactions generated by the direct contact between the positive electrode and the electrolyte under current, which will greatly reduce the cycle stability of the battery system.

[0005] The problem of low energy density can be divided into two reasons. First, the positive electrode material often needs to add supporting electrolytes and conductive carbon, resulting in the positive electrode active material accounting for only 50%, which greatly loses the energy density. On the other hand, multi-electron transfer and voltage platform restrict each other, that is, high-capacity multi-electron transfer reactions often correspond to low voltage platforms, while materials with high voltage platforms often have lower capacity.

[0006] In summary, it is particularly important to research and develop a multi-electron transfer positive electrode material that has a high voltage platform and high specific capacity, improves energy density and has good cycle stability. Summary of the invention

[0007] In order to solve the problems existing in the prior art, the present invention discloses an all-solid-state lithium-ion battery positive electrode material, a preparation method and an application thereof. A halide positive electrode material with high energy density is synthesized by high-energy ball milling. At room temperature, after adding supporting electrolyte and conductive agent, it can be used in halide-based all-solid-state lithium-ion batteries.2 S+FeCl 3 LiFeCl obtained by high-speed ball milling 3 +S composite material, providing four reaction platforms to convert LiFeCl 3 The original specific capacity has been increased by 35%-40%, and the energy density has been increased by 50%-55%; the in-situ introduced S makes up for the LiFeCl 3 The voltage difference of nearly 2V from the deintercalation reaction platform to the conversion reaction platform is reduced to 1 V, which is more convenient for practical application. 3 Compared with the physical mixing method of S, in-situ generation of S can better ensure the S in LiFeCl 3 Adhesion and uniformity near the particles; the prepared composite positive electrode material has a stable interface with the electrolyte, and the assembled all-solid-state battery exhibits good cycle stability.

[0008] In a first aspect, the present invention provides a method for preparing a positive electrode material for an all-solid-state lithium-ion battery, the method comprising the following steps: Step 1), take Li 2 S and FeCl 3 Raw materials, mix well; Step 2) Under the protection of an inert atmosphere, the raw material obtained in step 1) is subjected to a high-energy ball milling reaction to obtain the positive electrode material.

[0009] Furthermore, in step 1), Li 2 S as lithium and sulfur source, FeCl 3 As a source of iron and chlorine; Li 2 S and FeCl 3 The molar ratio is (0.25-1):1, preferably 0.5-0.8:1; In step 2, the high-energy ball milling reaction comprises: placing the raw materials and ball milling beads into a ball milling jar, sealing it and filling it with an inert atmosphere, and then placing the ball milling jar in a high-energy ball mill for high-energy ball milling reaction; The ratio of the total mass of the raw materials to the total mass of the ball milling beads is 1: (30-100), preferably 1: (70-75); In the high-energy ball milling reaction, the ball milling speed is 1000-2000 rpm, preferably 1000-1200 rpm; the ball milling reaction time is 10-100 h, preferably 20-30 h.

[0010] Furthermore, the inert atmosphere is high-purity argon gas, the purity of the high-purity argon gas is greater than 99.999%, and the content of oxygen and water is less than 0.01 ppm.

[0011] In a second aspect, the present invention provides an all-solid-state lithium-ion battery positive electrode material prepared according to the above method.

[0012] In a third aspect, the present invention provides a use of the positive electrode material as a positive electrode active ingredient in a positive electrode of an all-solid-state lithium-ion battery.

[0013] In a fourth aspect, the present invention provides an all-solid-state lithium-ion battery composite positive electrode, wherein the all-solid-state lithium-ion battery composite positive electrode comprises the high energy density positive electrode material, a conductive agent and a supporting electrolyte.

[0014] Furthermore, the conductive agent includes one or more of carbon nanotubes, carbon nanofibers, graphene, SuperP, Ketjen black, acetylene black, and activated carbon, and the mass of the conductive agent accounts for 5%-10% of the total mass of the composite electrode; the supporting electrolyte includes Li 2 ZrCl 6 , Li 6 PS 5 Cl, the mass of the supporting electrolyte accounts for 20%-25% of the total mass of the composite electrode.

[0015] In a fifth aspect, the present invention provides an all-solid-state lithium-ion battery, wherein the all-solid-state lithium-ion battery comprises the all-solid-state lithium-ion battery composite positive electrode as a positive electrode.

[0016] The solid electrolyte of the all-solid-state lithium-ion battery is Li 2 ZrCl 6 and Li 6 PS 5 Cl double-layer stacked electrolyte, the negative electrode is lithium metal foil.

[0017] The positive electrode of the present invention has four-stage reaction platforms with small voltage difference between the platforms, considerable energy density and good cycle stability.

[0018] The beneficial effects of the present invention are: (1) The present invention prepares a multi-electron transfer cathode material with high energy density by high-energy ball milling. Compared with other chlorine-based cathode materials, the energy density has obvious advantages; (2) The high energy density multi-electron transfer cathode material described in the present invention only needs to be compounded with 5% conductive carbon and 25% supporting electrolyte to be applied to all-solid-state lithium-ion batteries. Compared with sulfur-based cathode materials, the proportion of active substances has obvious advantages.

[0019] (3) The high energy density multi-electron transfer cathode material described in the present invention is superior to LiFeCl 3 The material reduces its original voltage difference of nearly 2 V to 1 V, significantly improves the energy density, and has good cycle stability; (4) The high energy density multi-electron transfer cathode material described in the present invention is synthesized only by high-speed ball milling, which has a relatively simple process and good prospects for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The positive electrode material Li prepared in Example 2 2 S+xFeCl 3 (x=2), SEM image of the positive electrode material LFSC prepared in Example 6; Figure 2 The positive electrode material Li prepared in Example 1, Example 2, Example 3, and Example 4 2 S+xFeCl 3 X-ray diffraction patterns of (x=1, 2, 3, 4); Figure 3 TEM image of the positive electrode material prepared in Example 6; Figure 4 The positive electrode material Li prepared in Example 2 2 S+xFeCl 3 (x=2) and the Raman signal test graph of the material prepared in Comparative Example 1; Figure 5 The positive electrode material Li of Example 2 2 S+xFeCl 3 (x=2) Mössbauer spectrum; Figure 6 The charge and discharge curves of the multi-electron transfer cathode materials prepared in Example 1, Example 2, Example 3, and Example 4 in a halide-based all-solid-state lithium-ion battery; Figure 7 The charge and discharge curves of the high energy density multi-electron transfer positive electrode materials prepared in Example 5, Example 6, Example 7 and Example 8 in the halide-based all-solid-state lithium-ion battery; Figure 8 The charge and discharge curves of the composite positive electrode materials prepared for Comparative Examples 2 and 4 in halide-based all-solid-state lithium-ion batteries; Fig. 9 The rate performance diagram of the positive electrode material prepared in Example 6 in a halide-based all-solid-state lithium-ion battery; Fig.10 Cyclic performance diagram of positive electrode materials prepared for Example 6, Comparative Example 5 and Comparative Example 4 in halide-based all-solid-state lithium-ion batteries; Fig.11 The charge and discharge curves of the multi-electron transfer positive electrode material prepared in Example 9 in a halide-based all-solid-state lithium-ion battery. DETAILED DESCRIPTION

[0021] The present invention is described in detail below with reference to the embodiments, but the embodiments of the present invention are not limited thereto. Obviously, the embodiments described below are only partial embodiments of the present invention. For those skilled in the art, other similar embodiments obtained without creative labor all fall within the protection scope of the present invention.

[0022] The present invention is described in detail below with reference to the embodiments, but the embodiments of the present invention are not limited thereto. Obviously, the embodiments described below are only partial embodiments of the present invention. For those skilled in the art, other similar embodiments obtained without creative labor all fall within the protection scope of the present invention.

[0023] Synthesis of electrolyte Supporting electrolyte Li 2 ZrCl 6 Synthesis: According to the formula 2LiCl+ZrCl 4 Molar ratio. Weigh 0.4 g of dried LiCl and 1.1 g of ZrCl 4 , put into a zirconia ball milling jar with a volume of 100 mL, then add 110 g of zirconia ball milling beads, and strictly seal the ball milling jar in a glove box to ensure an inert dry atmosphere of argon gas in the jar; then place the sealed ball milling jar in a ball mill and fix it; then set the program for high-speed ball milling. The specific process of high-energy ball milling reaction is: ball milling speed 1000 rpm, ball milling reaction time 24 h, and open the ball milling jar in the glove box every 4 hours for mixing. Finally, the electrolyte Li 2 ZrCl 6 ; Another mention of Li 6 PS 5 The Cl supporting electrolyte was commercially available from the National Automobile Power Research Institute.

[0024] Example 1 Synthesis of high energy density multi-electron transfer cathode material precursor: According to the formula Li 2 S+xFeCl 3 (x=1, represents FeCl 3 Mole number, Li 2 Weigh 0.331 g Li 2 S and 1.169 g anhydrous FeCl 3; put them into 100 mL zirconia ball mill jars respectively, then add 110 g zirconia ball mill beads into each ball mill jar, and strictly seal the ball mill jars in the glove box to ensure the argon inert dry atmosphere in the jars; then place the sealed ball mill jars in the ball mill and fix them; then set the program for high-speed ball milling. The specific process of high-energy ball milling reaction is as follows: ball milling speed of 1000 rpm, ball milling reaction time of 24 h, and open the ball mill jar in the glove box every 4 hours for mixing. Finally, collect the materials to prepare the positive electrode material Li 2 S+xFeCl 3 (x=1).

[0025] Synthesis of multi-electron transfer positive electrode material: Weigh 0.19 g of the above-obtained positive electrode material, add 0.01 g of conductive agent (acetylene black), put all into a ball mill with a volume of 100 mL, then add 110 g of zirconia ball milling beads, and strictly seal the ball mill in a glove box to ensure an inert dry atmosphere of argon gas in the jar; then place the sealed ball mill in a ball mill and fix it; then perform low-speed ball milling at a ball milling speed of 180 rpm; the multi-electron transfer positive electrode material can be prepared.

[0026] Example 2

[0027] Synthesis of high energy density multi-electron transfer cathode material precursor: According to the formula Li 2 S+xFeCl 3 (x=2, represents FeCl 3 Mole number, Li 2 Weigh 0.186 g Li 2 S and 1.314 g anhydrous FeCl 3 ; put them into 100 mL zirconia ball mill jars respectively, then add 110 g zirconia ball mill beads into each ball mill jar, and strictly seal the ball mill jars in the glove box to ensure the argon inert dry atmosphere in the jars; then place the sealed ball mill jars in the ball mill and fix them; then set the program for high-speed ball milling. The specific process of high-energy ball milling reaction is as follows: ball milling speed of 1000 rpm, ball milling reaction time of 24 h, and open the ball mill jar in the glove box every 4 hours for mixing. Finally, collect the materials to prepare the positive electrode material Li 2 S+xFeCl 3 (x=2).

[0028] Synthesis of multi-electron transfer positive electrode material: Weigh 0.19 g of the above-obtained positive electrode material, add 0.01 g of conductive agent (acetylene black), put all into a ball mill with a volume of 100 mL, then add 110 g of zirconia ball milling beads, and strictly seal the ball mill in a glove box to ensure an inert dry atmosphere of argon gas in the jar; then place the sealed ball mill in a ball mill and fix it; then perform low-speed ball milling at a ball milling speed of 180 rpm; the multi-electron transfer positive electrode material can be prepared.

[0029] Example 3

[0030] Synthesis of high energy density multi-electron transfer cathode material precursor: According to the formula Li 2 S+xFeCl 3 (x=3, represents FeCl 3 Mole number, Li 2 Weigh 0.129 g Li 2 S and 1.371 g anhydrous FeCl 3 ; put them into 100 mL zirconia ball mill jars respectively, then add 110 g zirconia ball mill beads into each ball mill jar, and strictly seal the ball mill jars in the glove box to ensure the argon inert dry atmosphere in the jars; then place the sealed ball mill jars in the ball mill and fix them; then set the program for high-speed ball milling. The specific process of high-energy ball milling reaction is as follows: ball milling speed of 1000 rpm, ball milling reaction time of 24 h, and open the ball mill jar in the glove box every 4 hours for mixing. Finally, collect the materials to prepare the positive electrode material Li 2 S+xFeCl 3 (x=3).

[0031] Synthesis of multi-electron transfer positive electrode material: Weigh 0.19 g of the above-obtained positive electrode material, add 0.01 g of conductive agent (acetylene black), put all into a ball mill with a volume of 100 mL, then add 110 g of zirconia ball milling beads, and strictly seal the ball mill in a glove box to ensure an inert dry atmosphere of argon gas in the jar; then place the sealed ball mill in a ball mill and fix it; then perform low-speed ball milling at a ball milling speed of 180 rpm; the multi-electron transfer positive electrode material can be prepared.

[0032] Example 4

[0033] Synthesis of high energy density multi-electron transfer cathode material precursor: According to the formula Li 2 S+xFeCl 3 (x=4, represents FeCl 3 Mole number, Li 2Weigh 0.099 g Li 2 S and 1.401 g anhydrous FeCl 3 ; put them into 100 mL zirconia ball mill jars respectively, then add 110 g zirconia ball mill beads into each ball mill jar, and strictly seal the ball mill jars in the glove box to ensure the argon inert dry atmosphere in the jars; then place the sealed ball mill jars in the ball mill and fix them; then set the program for high-speed ball milling. The specific process of high-energy ball milling reaction is as follows: ball milling speed of 1000 rpm, ball milling reaction time of 24 h, and open the ball mill jar in the glove box every 4 hours for mixing. Finally, collect the materials to prepare the positive electrode material Li 2 S+xFeCl 3 (x=4).

[0034] Synthesis of multi-electron transfer positive electrode material: Weigh 0.19 g of the above-obtained positive electrode material, add 0.01 g of conductive agent (acetylene black), put all into a ball mill with a volume of 100 mL, then add 110 g of zirconia ball milling beads, and strictly seal the ball mill in a glove box to ensure an inert dry atmosphere of argon gas in the jar; then place the sealed ball mill in a ball mill and fix it; then perform low-speed ball milling at a ball milling speed of 180 rpm; the multi-electron transfer positive electrode material can be prepared.

[0035] Embodiment 5-8 Synthesis of high energy density multi-electron transfer cathode materials: Weigh 0.14 g of each of the synthesized multi-electron transfer cathode materials in Examples 1-4, add 0.05 g of Li 2 ZrCl 6 The supporting electrolyte and 0.01 g of conductive agent (acetylene black) were added, and then 110 g of zirconium oxide ball milling beads were added thereto, and the ball milling jar was strictly sealed in the glove box to ensure the argon inert dry atmosphere in the jar; the sealed ball milling jar was subsequently placed in a ball mill and fixed; low-speed ball milling was then performed, and the ball milling speed was 552 rpm; the composite positive electrode material was prepared, and x was recorded from small to large as Examples 5, 6, 7, and 8. Among them, for the convenience of description, Example 6 is called LFSC.

[0036] Example 9

[0037] According to the formula Li 2 S+2FeCl 3 (Li 2 The molar fraction ratio of S is 1). Weigh 0.186 gLi 2 S and 1.314 g anhydrous FeCl 3, put it into a zirconia ball milling jar with a volume of 100 mL, then add 110 g of zirconia ball milling beads into each ball milling jar, and strictly seal the ball milling jar in a glove box to ensure an inert dry atmosphere of argon gas in the jar; subsequently place the sealed ball milling jar in a ball mill and fix it; then set the program for high-speed ball milling. The specific process of high-energy ball milling reaction is: ball milling speed of 2000 rpm, ball milling reaction time of 24 h, and finally collect the material to prepare the cathode material precursor.

[0038] Weigh 0.14 g of the above cathode material precursor and add 0.05 g Li 2 ZrCl 6 The supporting electrolyte and 0.01 g agent (acetylene black) were placed in a 100 mL ball mill, followed by the addition of 110 g zirconia ball mill beads, and the ball mill was tightly sealed in a glove box to ensure an inert dry atmosphere of argon gas in the mill. The sealed ball mill was then placed in a ball mill and fixed. Low-speed ball milling was then performed at a speed of 552 rpm to prepare a multi-electron transfer cathode material, which was recorded as LFSC-2000 rpm.

[0039] Comparative Example 1 Commercially available S (SIGMA-ALDRICH, 99.5%-100.5%) was weighed, evacuated and transferred to a glass bottle, which was then transferred to a glove box.

[0040] Comparative Example 2 LiFeCl 4 Cathode material synthesis: weigh 0.311 g of dried LiCl and 1.189 g of anhydrous FeCl 3 All of them were put into a 100 mL zirconia ball mill, and then 110 g of zirconia ball mill beads were added. The ball mill was strictly sealed in a glove box to ensure an inert dry atmosphere of argon gas in the jar. The sealed ball mill was then placed in a ball mill and fixed. The program was then set for high-speed ball milling. The specific process of the high-energy ball milling reaction was a ball milling speed of 1000 rpm and a ball milling reaction time of 24 h. The ball mill was opened in the glove box every 4 hours for mixing, and then repeated 6 times to prepare the cathode material precursor.

[0041] Weigh 0.14 g of the sample (positive electrode material precursor) obtained above, add 0.05 g Li 2 ZrCl 6The supporting electrolyte and 0.01 g of conductive agent (acetylene black) were all put into a 100 mL ball mill, and then 110 g of zirconium oxide ball mill beads were added. The ball mill was strictly sealed in a glove box to ensure an argon inert dry atmosphere in the jar. The sealed ball mill was then placed in a ball mill and fixed. Low-speed ball milling was then performed at a ball milling speed of 552 rpm to prepare the positive electrode material LiFeCl 4 .

[0042] Comparative Example 3 LiFeCl 3 Synthesis of positive electrode materials Weigh 0.376 g of dried LiCl and 1.124 g of anhydrous FeCl 2 All of them were put into a 100 mL zirconia ball mill jar, and then 110 g of zirconia ball mill beads were added thereto, and the ball mill jar was strictly sealed in a glove box to ensure an inert dry atmosphere of argon gas in the jar; the sealed ball mill jar was subsequently placed in a ball mill and fixed; the program was then set for high-speed ball milling. The specific process of the high-energy ball milling reaction was as follows: a ball milling speed of 1000 rpm and a ball milling reaction time of 24 h; the ball mill jar was opened in the glove box every 4 hours for mixing, and then repeated 6 times to prepare the cathode material precursor.

[0043] Comparative Example 4 Weigh 0.18 g of the sample (positive electrode material precursor) obtained in Comparative Example 3, add 0.02 g of conductive agent (acetylene black), and put all of them into a ball mill with a volume of 100 mL. Then, 110 g of zirconium oxide ball milling beads are added thereto, and the ball mill is strictly sealed in a glove box to ensure an argon inert dry atmosphere in the jar; then, the sealed ball mill is placed in a ball mill and fixed; then, low-speed ball milling is performed at a ball milling speed of 180 rpm; the positive electrode material LiFeCl 3 .

[0044] Comparative Example 5 LiFeCl 3 Preparation of simple mixed S cathode material: According to 2LiFeCl 3 +S formula, weigh the sample of comparative example 3 (LiFeCl 3) 1.370 g and 0.130 g of sample (S) of comparative example 1 were all put into a zirconia ball mill with a volume of 100 mL, and then 110 g of zirconia ball mill beads were added thereto, and the ball mill was strictly sealed in a glove box to ensure an inert dry atmosphere of argon gas in the jar; then the program was set for high-speed ball milling, and the specific process of the high-energy ball milling reaction was as follows: a ball milling speed of 1000 rpm and a ball milling reaction time of 24 h; the ball mill was opened in the glove box every 4 hours for mixing, and then repeated 6 times to prepare the positive electrode material precursor.

[0045] Then weigh 0.14 g of the precursor and add 0.05 g of Li 2 ZrCl 6 The supporting electrolyte and 0.01 g of conductive agent (acetylene black) were all put into a 100 mL zirconia ball mill, and then 110 g of zirconia ball mill beads were added. The ball mill was strictly sealed in a glove box to ensure an argon inert dry atmosphere. The sealed ball mill was then placed in a ball mill and fixed. Low-speed ball milling was then performed at a ball milling speed of 552 rpm. The material was collected to obtain 2LiFeCl 3 +S material.

[0046] Comparative Examples 6-7 According to the formula Li 2 S+2FeCl 3 (Li 2 The molar fraction ratio of S is 1). Weigh 0.186 gLi 2 S and 1.314 g anhydrous FeCl 3 , put it into a zirconia ball mill with a volume of 100 mL, and then add 110 g of zirconia ball mill beads to each ball mill. The materials in the two ball mills are the same, and the ball mills are strictly sealed in a glove box to ensure an inert dry atmosphere of argon gas in the jar; subsequently, the sealed ball mill is placed in a ball mill and fixed; then the program is set for high-speed ball milling. The specific process of the high-energy ball milling reaction is as follows: for comparative example 6, the ball milling speed is 300 rpm, and the ball milling reaction time is 24 h; for comparative example 7, the ball milling speed is 1000 rpm, and the ball milling reaction time is 4 h. Finally, the material is collected to prepare the positive electrode material.

[0047] All-solid-state lithium-ion battery assembly A cylindrical battery mold with an inner diameter of 10 mm was used, and 50 mg of the above-mentioned Li 2 ZrCl 6 The supporting electrolyte was maintained at 0.5 t pressure for 2 min, and then 50 mg of Li 6 PS 5 Cl supported electrolyte, maintained at 1 t pressure for 2 min, and then2 ZrCl 6 2.5 mg of positive electrode material (Examples 1-13, Comparative Examples 2, 4, and 5) was spread on the side, flattened with tweezers, and then covered with aluminum sheet on the positive electrode material. The pressure was maintained at 4 t for 2 min, and then the Li 6 PS 5 Add a lithium sheet to the Cl side, and then add a copper sheet with the same diameter of 10 mm on the lithium sheet. Finally, put the assembled battery core into the mold, maintain a pressure of 0.5 t and tighten it. You can get an assembled all-solid-state lithium-ion battery.

[0048] The prepared positive electrode materials and batteries were tested, and the results are as follows: Experimental results analysis Figure 1 The SEM image shows that the positive electrode material Li obtained in Example 2 2 S+xFeCl 3 (x=2) The particles are spherical and are composed of small granular materials stacked together. This is due to the LiFeCl 3 With the accumulation of amorphous S, LiFeCl 3 The amorphous sulfur element is evenly distributed near the accumulated particles and the two have good adhesion. The diameter of the large particles is 6~10 microns, and then Li is added. 2 ZrCl 6 The particle size of Example 6 is slightly increased.

[0049] Figure 2 It was observed that the main peak positions of samples in Examples 1, 2, 3, and 4 were similar to those of LiFeCl 3 The crystal structure corresponds well, proving that high-speed ball milling can be used to convert Li 2 S and FeCl 3 The two precursors react to form this characteristic crystal structure.

[0050] Figure 3 df can be observed from the morphology of LFSC Example (6) of 500nm and nearly 100nm. From the outside, the surface of the particles is covered with a thin layer of amorphous sulfur, and the surface of the large particles is composed of stick-like particles LiFeCl 3 The accumulation is consistent with the conclusion of SEM image. Figure 3 The existence of (1 1 1) crystal plane can be clearly observed in ac, corresponding to 0.6 nm, and there are multiple disconnections, dislocations, and distortions on the surface, which corresponds to the non-periodic characteristics of halides obtained by mechanical ball milling. In addition, the (2 2 2) crystal plane corresponding to 0.3 nm and the (4 0 0) crystal plane corresponding to 0.26 nm can be observed. This is consistent with the conclusion of XRD.

[0051] Figure 4 The Raman test was conducted at 532 nm light with 5% light intensity for 60 s to measure the positive electrode material Li prepared in Example 2. 2 S+xFeCl 3 (x=2); the material obtained in comparative example 1 was measured with a light intensity of 0.1% and an exposure of 30 s. The Raman signal of LFSC corresponds well to the sublimated sulfur, proving that the high-speed ball milling process reacts to make the precursor Li 2 S and FeCl 3 The S element is obtained by transformation.

[0052] Figure 5 The Mössbauer spectroscopy test proves that the positive electrode material Li 2 S+xFeCl 3 (x=2) The sample iron exists in the form of divalent iron, combined with Figure 4 The Raman data shown in the figure prove that the high-speed ball milling process makes Li 2 S and FeCl 3 Conversion to LiFeCl 3 With S product.

[0053] Figure 6 The all-solid-state lithium-ion battery assembled with the positive electrode materials of Examples 1, 2, 3, and 4 was tested at 0.1 mA cm -2 The first three cycles of charge-discharge curve test all showed charge-discharge curves with four electron transfer platforms, with a specific capacity of 200 mAh g -1 ~500 mAh g -1 interval.

[0054] Figure 7 The all-solid-state lithium-ion battery assembled with the positive electrode materials of Examples 5, 6, 7, and 8 was tested at 0.1 mA cm -2 In the first three cycles of the charge-discharge curve test, the charge-discharge curves of Examples 5, 6, and 8 all have a charge-discharge capacity of more than 600 mAh g at this current. -1 The first cycle discharge capacity is significantly improved compared with Examples 1-4 and Comparative Example 4, among which Example 6 has the highest energy density, reaching about 1414 Whkg -1 .

[0055] Figure 8 The all-solid-state lithium-ion battery assembled with the cathode materials of Comparative Examples 2 and 4 was tested at 0.1 mA cm -2 From the first three cycles of the charge-discharge curve test, it can be observed that there is a voltage difference of about 1.7 V between the first discharge platform and the second discharge platform of this series of materials.

[0056] Examples 1-8 all present a new discharge platform in the range of 2.2 V-2.6 V. Compared with the materials of Comparative Examples 2 and 4, the platform voltage difference of up to 2 V is reduced to 1 V, which is beneficial to the application of battery systems in practical applications.

[0057] Fig. 9 The all-solid-state lithium-ion battery assembled with the positive electrode material of Example 6 was -1 , 0.2 mA cm -1 , 0.5 mA cm -1 , 1.0 mA cm -1 , 2.0 mA cm -1 , 0.1 mA cm -1 The rate performance test curve of charge and discharge cycle under current conditions, the material of Example 6 at 0.5 mA cm -1 The current still has about 400 mAh g -1 The discharge capacity of the cathode material is improved by utilizing the high capacity cathode material for practical application.

[0058] Fig.10 After Example 6 and Comparative Examples 4 and 5 were assembled into all-solid-state lithium-ion batteries, the -1 The current was run for three cycles and then increased to 0.3 mA cm -1 , a long cycle charge and discharge curve test was conducted. By comparison, it was observed that Example 6 not only had a more obvious advantage in discharge capacity, but also had a very superior cycle stability. 3 After 250 cycles, the capacity retention rate of the material is about 55%, while the capacity of the LFSC composite positive electrode of Comparative Example 4 drops to 0 after 250 cycles; the simple mixed 2LiFeCl 3 The capacity of the +S positive electrode drops sharply after only about 80 cycles, which reflects the advantages of the article's composite S positive electrode material method.

[0059] Fig.11 Example 9 also achieved the charge-discharge curve effect of Example 6, proving the rationality of the ball milling speed of 1000-2000 rpm. However, due to the too low speed and ball milling time, the Li 2 S has not yet reacted with FeCl 3 Complete response, only partial effect or no response.

Claims

1. A method for preparing a positive electrode material for an all-solid-state lithium-ion battery, characterized in that: The method comprises the following steps: Step 1), take Li2S and FeCl3 raw materials and mix them evenly; Step 2) Under the protection of an inert atmosphere, the raw material obtained in step 1) is subjected to a high-energy ball milling reaction to obtain the positive electrode material.

2. The method for preparing the positive electrode material of an all-solid-state lithium-ion battery according to claim 1, characterized in that: In step 1), the molar ratio of Li2S to FeCl3 is (0.25-1):1; In step 2), the high-energy ball milling reaction comprises: placing the raw materials and ball milling beads into a ball milling jar, sealing it and filling it with an inert atmosphere, and then placing the ball milling jar in a high-energy ball mill for high-energy ball milling reaction; Among them, the ratio of the total mass of raw materials to the total mass of ball milling beads is 1: (30-100); In the high-energy ball milling reaction, the ball milling speed is 1000-2000 rpm; the ball milling reaction time is 10-100 h.

3. The method for preparing the positive electrode material of an all-solid-state lithium-ion battery according to claim 1, characterized in that: The inert atmosphere is high-purity argon gas, the purity of the high-purity argon gas is greater than 99.999%, and the content of oxygen and water is less than 0.01 ppm.

4. An all-solid-state lithium-ion battery positive electrode material prepared by the preparation method according to any one of claims 1 to 3.

5. Use of the positive electrode material according to claim 4 as a positive electrode active component in a positive electrode of an all-solid-state lithium-ion battery.

6. An all-solid-state lithium-ion battery composite positive electrode, characterized in that: The all-solid-state lithium-ion battery composite positive electrode comprises the all-solid-state lithium-ion battery positive electrode material according to claim 4, and also comprises a conductive agent and a supporting electrolyte.

7. The all-solid-state lithium-ion battery composite positive electrode according to claim 6, characterized in that: The conductive agent includes one or more of carbon nanotubes, carbon nanofibers, graphene, SuperP, Ketjen black, acetylene black, and activated carbon, and the mass of the conductive agent accounts for 5%-10% of the total mass of the composite electrode; The supporting electrolyte includes one or two of Li2ZrCl6 and Li6PS5Cl; the mass of the supporting electrolyte accounts for 20%-25% of the total mass of the composite electrode.

8. An all-solid-state lithium-ion battery, characterized in that: The all-solid-state lithium-ion battery comprises the all-solid-state lithium-ion battery composite positive electrode according to claim 6 as a positive electrode.

9. The all-solid-state lithium-ion battery according to claim 8, characterized in that: The solid electrolyte of the all-solid-state lithium-ion battery is a double-layer stacked electrolyte composed of Li2ZrCl6 and Li6PS5Cl, and the negative electrode is a lithium metal foil.

10. The all-solid-state lithium-ion battery according to claim 8, characterized in that: The positive electrode has four reaction platforms with small voltage difference between the platforms, considerable energy density and good cycle stability.

Citation Information

Patent Citations

  • Preparation method of all-solid-state lithium battery positive electrode

    CN110048083A

  • Doped phosphorus-sulfur iodide solid electrolyte and preparation method and application thereof

    CN111092262A

  • Halide-based positive electrode active material as well as synthesis method and application thereof

    CN116799201A

  • Chloride-based positive electrode material and application thereof in solid-state lithium battery

    CN118108248A

  • Nonaqueous electrolyte secondary battery

    JP2006164695A